STRATEGY TO IMPROVE QUR'AN MEMORIZATION OF STUDENTS AT RUMAH QUR'AN MULIA BEKASI - Rahmat, Muhammad Nur; Suharsiwi, Suharsiwi; Yumna, Laila (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
This study explores the teaching strategies for memorizing the Qur'an applied at Rumah Qur'an Mulia Bekasi, an educational institution established to develop students' potential in memorizing the Qur'an. The research method used is qualitative with a case study approach, involving in-depth interviews with the founder and teachers and direct observation of the learning process. The study results indicate that Rumah Qur'an Mulia applies the 5T method (Tahsin, Tahfidz, Tamyiz, Tafsir, and Taklim), which is structured and planned and involves the active participation of students in the learning process. The extraordinary ability of the students at Rumah Qu'an Mulia Bekasi was to memorize the Qur'an within 1 year. In addition, the motivation of parents to entrust their children to Rumah Qur'an Mulia Bekasi is in addition to becoming memorizers of the Qur'an, having good morals, and being useful for life in society. These findings are expected to support the development of Qur'an education in Indonesia and serve as a valuable reference for other educational institutions in enhancing the quality of Qur'an memorization instruction.